Mendeteksi adanya financial distress dari rasio keuangan dengan kondisi inflasi dan suku bunga sebagai variable moderasi pada perusahaan BUMN sektor aneka industry - PUTERI, NISRINA RANIA (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the potential occurrence of financial distress in state-owned enterprises within the diversified industry sector by analyzing financial ratios, with inflation and interest rates as moderating variables. The research applies a descriptive approach combined with logit regression analysis. The results reveal that liquidity, profitability, and leverage ratios significantly contribute to predicting financial distress. Furthermore, inflation and interest rates are shown to strengthen the relationship between financial ratios and the likelihood of financial distress. These findings highlight the necessity for companies to consistently monitor internal financial performance while also considering macroeconomic conditions in order to anticipate financial difficulties at an early stage. The results of this study provide practical implications for state-owned enterprise management in formulating financial risk mitigation strategies and financial planning that are more adaptive to economic changes. Furthermore, these findings can serve as a reference for regulators and stakeholders in developing policies that support the stability and sustainability of company operations amidst macroeconomic dynamics.